2020
DOI: 10.1002/lio2.428
|View full text |Cite
|
Sign up to set email alerts
|

Navigating telemedicine for facial trauma during the COVID‐19 pandemic

Abstract: Importance The COVID‐19 pandemic is changing how health care providers practice. As some telemedicine and telecommunication support tools have been incorporated into the otolaryngology practice in response to safety and access demands, it is essential to review how these tools and services can help facilitate facial trauma evaluation during a time when clinical resources are limited. Objective To review applications of telemedicine for the evaluation of facial trauma to better direct utilization of these metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…It was especially critical to implement telemedicine within laryngology clinics given the initial concern about potentially aerosol generating procedures such as laryngoscopy during the COVID-19 pandemic. [1][2][3] Previous studies have reported high satisfaction rates with telemedicine among patients and otolaryngologists. [4][5][6][7][8][9][10] Telemedicine has been utilized in otolaryngology clinics by a diverse population, with no difference in demographics, insurance, and socioeconomic level between patients seen during the pandemic and patients seen during the same time period in previous years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was especially critical to implement telemedicine within laryngology clinics given the initial concern about potentially aerosol generating procedures such as laryngoscopy during the COVID-19 pandemic. [1][2][3] Previous studies have reported high satisfaction rates with telemedicine among patients and otolaryngologists. [4][5][6][7][8][9][10] Telemedicine has been utilized in otolaryngology clinics by a diverse population, with no difference in demographics, insurance, and socioeconomic level between patients seen during the pandemic and patients seen during the same time period in previous years.…”
Section: Introductionmentioning
confidence: 99%
“…It was especially critical to implement telemedicine within laryngology clinics given the initial concern about potentially aerosol generating procedures such as laryngoscopy during the COVID‐19 pandemic. 1 , 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…Hence, measuring the satisfaction of physicians and patients towards virtual services is essential. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“… 20 During and after the pandemic, the utilization of a telemedicine consultation program between emergency department providers and maxillofacial specialists may help reduce unnecessary interventions, freeing up specialists to focus on higher acuity cases. 15 , 18 , 19 , 21 , 22 …”
Section: Preoperative Evaluationmentioning
confidence: 99%